Perioperative Outcomes and Surgical Case Volume in Pediatric Complex Cranial Vault Reconstruction: A Multicenter Observational Study From the Pediatric Craniofacial Collaborative Group. (October 2019) - Fernandez, Allison M.; Reddy, Srijaya K.; Gordish-Dressman, Heather; Muldowney, Bridget L.; Martinez, José Luis; Chiao, Franklin; Stricker, Paul A.; Abruzzese, Christopher; Apuya, Jesus; Beethe, Amy; Benzon, Hubert; Binstock, Wendy; et al.
Abstract : BACKGROUND: Complex cranial vault reconstruction (CCVR) performed to treat craniosynostosis can be associated with significant blood loss, transfusion, and perioperative complications. The aim of this study was to examine the effect of CCVR surgical case volume on perioperative outcomes. We hypothesized that surgical case volume is not associated with differences in perioperative outcomes. The study primary outcome was total perioperative blood donor exposures. Secondary outcomes included the total perioperative transfusion volume, major complications, and intensive care unit and hospital length of stay. METHODS: The multicenter Pediatric Surgery Perioperative Registry was queried for infants and children undergoing CCVR between June 2012 and September 2016. Institutions were categorized into low, middle, or high surgical case volume groups based on tertiles of the average number of cases performed per month. Primary and secondary outcomes were analyzed with respect to these groupings. RESULTS: The query yielded 1814 CCVR cases from 33 institutions. Demographics were similar among the 3 study groups. An inverse relationship between surgical case volume and total perioperative blood donor exposures was observed ( P < .001). The low-volume group had higher perioperative transfusion volumes ( P = .02 versus middle; P = .01 versus high). There was no significant relationship between surgical case volume and the incidence of major postoperative complications or hospital length of stay. CONCLUSIONS: In this study, low surgical case volumes were associated with increased total blood donor exposures and increased perioperative transfusion volumes. Hospital length of stay was homogeneous in the 3 groups, suggesting a limited overall clinical impact of the observed transfusion outcome differences.